2013
DOI: 10.3402/ijch.v72i0.21266
|View full text |Cite
|
Sign up to set email alerts
|

“Double culturedness”: the “capital” of Inuit nurses

Abstract: BackgroundThe health and educational systems in Greenland and Nunavut are reflections of those in Denmark and Southern Canada, with the language of instruction and practise being Danish and English. This places specific demands on Inuit studying nursing.ObjectiveThis paper discusses the experiences of Inuit who are educated in nursing programmes and practise in healthcare systems located in the Arctic but dominated by EuroCanadian and Danish culture and language.DesignResearch was qualitative and ethnographic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…In the included papers, it was not necessarily clear how many hours of observations the results were based on; that is Møller wrote: ‘It (the fieldwork) was conducted in five Greenlandic and two Nunavut communities under an anthropological frame, with 12 months of fieldwork between August 2007 and June 2009’ (p. 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the included papers, it was not necessarily clear how many hours of observations the results were based on; that is Møller wrote: ‘It (the fieldwork) was conducted in five Greenlandic and two Nunavut communities under an anthropological frame, with 12 months of fieldwork between August 2007 and June 2009’ (p. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Between 1997 and 2001, I lived and worked as a community health and tuberculosis nurse and consultant in Nunavut: two years in Cape Dorset, and shorter periods in Igloolik, Pangnirtung, and Iqaluit. I have conducted master's research (Møller 2005) in two Nunavut communities and doctoral research in three communities in Nunavut and four in Greenland, and taught courses for the medical interpreter program in Nunavut and for the nursing program in Nuuk between 2002 and 2010. Over shorter periods between 2010 and 2013, I worked with and interviewed Greenlandic nurses in Nuuk for a book about nurses and nursing in Greenland (Møller 2014).…”
Section: Methodsmentioning
confidence: 99%
“…When nurses or students shared an experience that was not very positive, it would often be done outside the formal interview and in the form of a story. While doing research on sociocultural experiences with tuberculosis in Nunavut, I found that although some might share negative experiences with Southerners in casual conversations, interviewees would rarely say anything negative about Southerners, be they healthcare professionals or not, during formal interviews (Møller 2005). Bryld (1998) described similar experiences when Greenlanders had been interviewed about their being sent to Denmark to be raised in foster care.…”
Section: Linguistic Capital and A Culturally Safe Work Environmentmentioning
confidence: 99%
See 2 more Smart Citations